2017
DOI: 10.1016/j.envint.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Paternal and maternal urinary phthalate metabolite concentrations and birth weight of singletons conceived by subfertile couples

Abstract: Background Ortho-phthalates are known endocrine disruptors. Prenatal phthalate exposure has been inconsistently associated with fetal growth and infant birth weight; however, the effect of paternal and maternal preconception exposure remains understudied. Objectives To investigate associations of paternal and maternal preconception and maternal prenatal urinary phthalate metabolite concentrations with birth weight. Methods The study comprised 364 singletons born to 364 mothers and 195 fathers (195 couples)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 61 publications
(79 reference statements)
0
37
1
Order By: Relevance
“…[63][64][65] It is accepted that early disruption to peri-implantation processes such as alterations in embryo spacing or development, decidualization, and placentation may perpetuate throughout pregnancy, manifesting later as preterm birth, among other adverse outcomes. 66 Based on previous results from the EARTH Study team and those of others, including fertile populations, we hypothesize that an early action of DEHP metabolites at the ovary may interfere with normal fertility and implantation processes, 67,68 predisposing to a syndrome of complications throughout gestation that may be associated with altered placental function, 69,70 embryo and fetal growth restriction, 71 preeclampsia, 72 pregnancy loss, 73 and ultimately preterm birth. Of relevance for preventive care, this syndrome could have its roots in the preconception or periconception period.…”
Section: Discussionmentioning
confidence: 97%
“…[63][64][65] It is accepted that early disruption to peri-implantation processes such as alterations in embryo spacing or development, decidualization, and placentation may perpetuate throughout pregnancy, manifesting later as preterm birth, among other adverse outcomes. 66 Based on previous results from the EARTH Study team and those of others, including fertile populations, we hypothesize that an early action of DEHP metabolites at the ovary may interfere with normal fertility and implantation processes, 67,68 predisposing to a syndrome of complications throughout gestation that may be associated with altered placental function, 69,70 embryo and fetal growth restriction, 71 preeclampsia, 72 pregnancy loss, 73 and ultimately preterm birth. Of relevance for preventive care, this syndrome could have its roots in the preconception or periconception period.…”
Section: Discussionmentioning
confidence: 97%
“…In a population-based birth cohort study in Spain (n=488 mother-child pairs), Casas et al showed that prenatal urinary MBzP concentrations were positively associated with birth weight among boys but not in girls. By contrast, three studies, including a prospective multiethnic cohort in New York city (n=404)(Wolff et al, 2008), a case-control study (n=191) in France,(Philippat et al, 2012) and a recent prospective study from the EARTH cohort (Messerlian et al, 2017) (n=321) reported that neither the individual prenatal phthalate metabolites nor the grouping of phthalate metabolites based on molecular weight were associated with birth weight. Of note, however, in the latter study (Messerlian et al, 2017), Messerlian et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bottlenose dolphin exposure to DEHP and DEP is concerning due to laboratory and human studies linking these chemicals to adverse health effects including altered hormone synthesis and transport (ATSDR, ; Meeker & Ferguson, ; Sathyanarayana et al, ], male genital developmental abnormalities (ATSDR, ; Swan, ), reproductive impairment (e.g., lower birth weight, Messerlian et al, ; preterm birth, Meeker et al, ; delayed time to pregnancy, Thomsen et al, ; pregnancy loss, H. Gao et al, ), and liver toxicoses including liver cancer (ATSDR, ). In fact, MEHP concentrations measured in the dolphins in this study (GM = 1.9 ng/ml; Range = 0.9–5.9 ng/ml) were at comparable levels reported to be associated with a reduced probability of reproductive success in humans (Hauser et al, ).…”
Section: Discussionmentioning
confidence: 99%